Good Corporate Governance dan Tax Management (Studi Empiris pada Perusahaan Perbankan yang Terdaftar Di BEI Tahun 2013-2015) - Yenni Carolina Carolina (Jurnal Akuntansi, 2017)
Abstract The purpose of this study is to examine the effect of good corporate governance (GCG)  using GCG mechanism to tax management. The sample used in this study was chosen based on purposive sampling, 18 banks listed on the Indonesia Stock Exchange in 2013-2015 with 54 observation data was collected as sampels. Data were analyzed using multiple linear regression analysis. Based on data processing, it can be seen that institutional ownership, managerial ownership, and audit committee have a positive effect on tax management, while independent commissioners have no effect on tax management. Keywords: GCG, Independent Commissioner and Audit Committee Tax Management, Institutional Ownership, Managerial Ownership